African islands : leading edges of empire and globalization - Falola, Toyin; Parrott, R. Joseph, 1985-; Sanchez, Danielle Porter, 1986- (Rochester studies in African history and the diaspora., 2019)
Explores the culturally complex and cosmopolitan histories and of islands off the African coast.